Efficacy of Bronchial Wash Cytology and its Correlation with Histopathology in Diagnosis of Lung Carcinoma in a Tertiary Care Hospital - Tomar, Shilpa; Thakur, Brijesh; Dubey, Krishna; Gulati, Priyanka (Annals of Pathology and Laboratory Medicine, 2021)
Introduction: Cytological evaluation is an important, usually initial diagnostic modality in patients with suspected malignant lung masses. Bronchoscopic washing, bronchoalveolar lavage, bronchial brushing and fine needle aspirations may complement tissue biopsies in the diagnosis of lung cancer. This study was undertaken to compare the efficacy of bronchial wash cytology and to correlate it with histopathology in diagnosis of suspected cases of lung cancer at a tertiary care hospital. Material and methods: Bronchial washings and bronchial biopsy were collected from total 60 clinically suspected cases of carcinoma lung. Bronchial washing smears were stained with MGG and H&E stain and were categorized as unequivocally positive / unequivocally negative for malignancy and atypical (equivocal for diagnosis). Biopsy sections were examined for histopathological diagnosis. Results: Cytomorphologically, 30 cases were reported as positive for malignancy, 28 cases were negative for malignancy and 02 cases were atypical. On histopathology, lung carcinoma was diagnosed in 48 patients out of them 35 cases were of squamous cell carcinoma, 7 cases were of small cell carcinoma and 6 were of large cell carcinoma. Conclusion: Maximum diagnostic yield can be obtained by combining biopsy with cytological procedures of washing rather alone.